Review of production responses from cows fed calcium salt of isobutyric and mixed 5-carbon volatile fatty acids - James R. Dunham (Kansas Agricultural Experiment Station Research Reports, 1986)
Recent developments in dairy cattle nutrition have resulted in the marketing of a calcium salt of isobutyric and mixed 5-carbon volatile fatty acids (IsoPlus®). The FDA approved product has been neutralized with calcium to form a dry salt of the acids, which are found naturally in the rumen. The following review of research results is intended as a guide for feeding IsoPlus®).; Dairy Day, 1986, Kansas State University, Manhattan, KS, 1986;
Keywords: Kansas Agricultural Experiment Station contribution; no. 87-88-S; Report of progress (Kansas Agricultural Experiment Station); 506; Dairy; Calcium salt; Isobutyric; Volatile fatty acid; Nutrition